Trophic Structure and Diet of Predatory Teleost Fishes in a Tropical Demersal Shelf Ecosystem - Speed, Conrad W.; Meekan, Mark G.; Birt, Matthew J.; Parsons, Miles J. G.; McLean, Dianne; Taylor, Brett M.; Thomas, Luke; McCauley, Robert; Semmens, Jayson M.; Newman, Stephen J. (Frontiers in Marine Science, 2022)
Predatory fishes are a major component of many tropical fisheries, although little is known about their diet and trophic structure, which can hinder effective management. We used stable isotopes δ15N and δ13C in conjunction with dietary prey items of five fishes (Lutjanus sebae, Lethrinus punctulatus, Epinephelus areolatus, Epinephelus multinotatus, and Plectropomus maculatus) to describe the diet and trophic structure across this assemblage. A total of 153 isotope and 87 stomach content samples were collected at two locations that were ≈30 km apart, over two sampling trips, separated by three months. There was clear separation of species’ mean δ15N and δ13C values in isotopic space; the highest mean δ15N was exhibited by E. multinotatus (13.50 ± 0.11 SE) and the lowest was L. punctulatus (11.05 ± 0.13). These two species had the lowest overlap of isotopic niche space, whereas the highest overlap occurred between L. sebae and P. maculatus. δ15N increased with fish body size for all species. However, body size was not significantly related to δ13C values for any species. There was a notable shift in both δ15N and δ13C between sampling trips, with δ13C being more depleted in the second trip. There was also a difference in δ13C between locations for all species, suggesting localised foraging. A multiple tissue comparison for L. sebae indicated positive relationships for both δ15N and δ13C between dorsal fin and muscle tissue. Mean δ15N values were the same for both fin (12.1 ± 0.10 SE) and muscle tissue (12.1 ± 0.09 SE), although δ13C was more enriched in fin (-15.6 ± 0.14 SE) compared to muscle tissue (-17.3 ± 0.11 SE). The most common dietary items across species were teleosts and crustaceans, which was consistent with isotope data indicating a reliance on a demersal food web (δ13C values ranging from -18 to -15‰). The results from our study indicate a dynamic spatio-temporal trophic structure and diet for commercially important demersal species and highlight the benefits of a multi-facetted sampling approach.